Trafficking Tantangan Bagi Indonesia - Khayati, Enny Zuhni (Musawa Jurnal Studi Gender dan Islam, 2006)
Human trafficking is currently a global issue. The reasons for conducting human trafficking include the low level of society knowledge and of skill abilities, the poverty, the limited available jobs, the high level of jobless people, and the weakness of law protection. The victims of human trafficking are mostly children (people under 18 year old) and women from poor families. They have to forcibly leave their safe hometown to work in dangerous working places. Most of them have been sexually exploited and trafficked for domestic work and receive unreasonable small payment. Their boss horribly treated them inhumanly. Trafficking is done by agents or sponsors: they work with worker recruiters/intermediaries particularly in villages. There have been a lot of efforts from governmental and non government institution to eliminate the human trafficking. But, the question is whether Indonesia has prioritized education and programs for the improvement of life skill in order to develop the quality of human resources to be able to eventually prevent human trafficking in Indonesia.